Effect of reaction solvent on hydroxyapatite synthesis in sol–gel process. Issue 12 (20th December 2017) - Nazeer, Muhammad Anwaar; Yilgor, Emel; Yagci, Mustafa Baris; Unal, Ugur; Yilgor, Iskender
Abstract : Synthesis of hydroxyapatite (HA) through sol–gel process in different solvent systems is reported. Calcium nitrate tetrahydrate (CNTH) and diammonium hydrogen phosphate (DAHP) were used as calcium and phosphorus precursors, respectively. Three different synthesis reactions were carried out by changing the solvent media, while keeping all other process parameters constant. A measure of 0.5 M aqueous DAHP solution was used in all reactions while CNTH was dissolved in distilled water, tetrahydrofuran (THF) and N, N -dimethylformamide (DMF) at a concentration of 0.5 M. Ammonia solution (28–30%) was used to maintain the pH of the reaction mixtures in the 10–12 range. All reactions were carried out at 40 ± 2°C for 4 h. Upon completion of the reactions, products were filtered, washed and calcined at 500°C for 2 h. It was clearly demonstrated through various techniques that the dielectric constant and polarity of the solvent mixture strongly influence the chemical structure and morphological properties of calcium phosphate synthesized. Water-based reaction medium, with highest dielectric constant, mainly produced β-calcium pyrophosphate (β-CPF) with a minor amount of HA. DMF/water system yielded HA as the major phase with a very minor amount of β-CPF. THF/water solvent system with the lowest dielectric constant resulted in the formation of pure HA.